2013
DOI: 10.1016/j.pain.2013.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Non-Hebbian plasticity at C-fiber synapses in rat spinal cord lamina I neurons

Abstract: SummaryThis study identified and characterized non-Hebbian type LTP in nociceptive pathways, a potential synaptic mechanism of secondary hyperalgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 63 publications
1
23
0
Order By: Relevance
“…Such a molecular diversity confers to these channels a variety of specific properties in different cell types and situations. VGCCs play a critical role in neuropathic pain development through the modulation of the release of excitatory neurotransmitters (31), calcium-dependent enzyme activation (32), gene regulation (32)(33)(34) and short-and long-term plasticity changes (35)(36)(37)(38). Abnormal regulation of VGCC subunits, such as α2δs, may contribute to pain signal transduction through several mechanisms including the induction of abnormal synaptogenesis (39,40).…”
Section: Disscussionmentioning
confidence: 99%
“…Such a molecular diversity confers to these channels a variety of specific properties in different cell types and situations. VGCCs play a critical role in neuropathic pain development through the modulation of the release of excitatory neurotransmitters (31), calcium-dependent enzyme activation (32), gene regulation (32)(33)(34) and short-and long-term plasticity changes (35)(36)(37)(38). Abnormal regulation of VGCC subunits, such as α2δs, may contribute to pain signal transduction through several mechanisms including the induction of abnormal synaptogenesis (39,40).…”
Section: Disscussionmentioning
confidence: 99%
“…long-term facilitation of endogenous motoneuronal phrenic or hypoglossal activity following episodic asphyxia (Baker & Mitchell, 2000;Mitchell et al, 2001;Baker-Herman & Mitchell, 2002;Bocchiaro & Feldman, 2004;Dale-Nagle et al, 2010;Baker-Herman & Strey, 2011). Another example of such plasticity would be LTP corresponding to central secondary hyperalgesia in pain pathways (Naka et al, 2013), as it was evoked in the absence of any presynaptic conditioning stimulation and without changes in active or passive properties of the neurons. A common feature of these forms of plasticity and of the effects of local spinal polarization is the tendency for the long-lasting facilitation to develop fairly slowly (Bolzoni & Jankowska, 2015) (Figs 2-7).…”
Section: Activity-independent Long-lasting DC Actionsmentioning
confidence: 99%
“…A common feature of these forms of plasticity and of the effects of local spinal polarization is the tendency for the long-lasting facilitation to develop fairly slowly (Bolzoni & Jankowska, 2015) (Figs 2-7). The same mechanisms might thus contribute to the post-polarization DC effects and to long-term facilitation or LTP, including changes in aamino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor function caused by 5-hydroxytryptamine (serotonin) (Bocchiaro & Feldman, 2004), a rise in the postsynaptic Ca 2+ level resulting from postsynaptic depolarization (Wyllie et al, 1994;Naka et al, 2013), or the effects of DC on vesicular glutamate transporters (Preobraschenski et al, 2014). However, the direct effects evoked during DC application and those following DC polarization differ in several respects, and may be, to some extent, attributable to different mechanisms.…”
Section: Activity-independent Long-lasting DC Actionsmentioning
confidence: 99%
“…It has also been reported that a rise in intracellular Ca 2+ levels of spinal lamina I neurons is enough to induce synaptic long‐term potentiation in the absence of any presynaptic stimulation (Naka et al . ).…”
Section: Discussionmentioning
confidence: 97%